LGG-11. ESTABLISHMENT OF A HUMAN 3-DIMENSIONAL LOW-GRADE GLIOMA TUMOR MODEL IN INDUCED PLURIPOTENT STEM CELL DERIVED BRAIN ORGANOIDS. (23rd April 2019) - Bahr, Annabelle; Capper, David; Witt, Olaf; Milde, Till; Selt, Florian; Buhl, Juliane; Stachelscheid, Harald; Driever, Pablo Hernáiz
Abstract: INTRODUCTION: Low-grade glioma (LGG) are the most common pediatric brain tumors. Preclinical models are still scarce. We used human induced pluripotent stem cell (hiPSC) derived brain organoids for human LGG disease modeling. METHODS: Brain organoids were generated from hiPSC cells using the STEMdiff™ Cerebral Organoid Kit (Stem Cell Technologies), based on the Lancaster et al. (Nature, 2013). LGG tumor spheres were generated from pilocytic astrocytoma cells DKFZ-BT66. High-grade glioma (HGG) tumor spheres were derived from U-87 cells. Brain organoids were co-cultured with either LGG or HGG tumor spheres. Co-cultures were formalin-fixed and paraffin-embedded for H&E and immunohistochemistry for analysis. RESULTS: Neuronal rosettes in the brain organoids represented immature and proliferating progenitor cells which were positive for MIB1. From day 30 to day 45, numbers of mature neurons expressing MAP2 increased. Organoids were focally expressing GFAP and S-100. After co-culturing tumor spheres with brain organoids (size ratio 1:1) we observed a partial or complete fusion of both tissues within the first three days. Red fluorescent protein expressing LGG cells migrated into the organoids. Their morphology resembled bipolar astrocytes and they invaded without destroying the normal organoid architecture. LGG cells strongly expressed MAP2 showing their differentiated character. In contrast, U-87 HGG cells massively spread around the organoids and showed a highly proliferating and invading biology. It was not possible to clearly discern remaining organoid tissue from HGG cells. Furthermore, we found a high rate of apoptotic cells. Co-cultured U-87 cells only expressed MIB1, especially in the outer cell layers, and no mature glial markers. CONCLUSIONS: We established the first human 3-dimensional LGG model in developing brain organoids, that allows animal free 3D LGG research. To better characterize the inter- and intracellular biology we will apply single-cell analysis.